Interactive Effects of Major Insect Pest of Watermelon on its Yield in Wukari, Nigeria - Emmanuel Okrikata; E. Oludele Ogunwolu; J. Itohan Otabor; A. Oyewole Ogunmola (مجلة بغداد للعلوم)
Watermelon is known to be infested by multiple insect pests both simultaneously and in sequence. Interactions by pests have been shown to have positive or negative, additive or non additive, compensatory or over compensatory effects on yields. Hardly has this sort of relationship been defined for watermelon vis-à-vis insect herbivores. A 2-year, 2-season (4 trials) field experiments were laid in the Research Farm of Federal University Wukari, to investigate the interactive effects of key insect pests of watermelon on fruit yield of Watermelon in 2016 and 2017 using natural infestations. The relationship between the dominant insect pests and fruit yield were determined by correlation (r) and linear regression (simple and multiple) analyses. Multimodel inference was used to define the predictor that impacted on fruit yield the most. Results indicated that, each pest had highly negative and significant (p < 0.05) impact on yield (range of r = -0.78 to -0.92), and that the coefficient of determination (R2) values (which were indicative of the effect of pests or their complexes on yield) did not rise on addition of interaction terms. This reveals a non additive negative impact of insect interactions on the fruit yield of watermelon. This may be due to among others; competition by the pest, phenology, plant defenses or changes in nutritional content of the plant. The need to therefore employ discriminate analysis to ascertain the contribution of each pest to yield loss when multiple pest infest a crop is thus highlighted.